2021
DOI: 10.1038/s41598-021-02957-x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the superior and inferior parietal lobes predicts inter-individual suitability for virtual reality

Abstract: The global virtual reality (VR) market is significantly expanding and being challenged with an increased demand owing to COVID-19. Unfortunately, VR is not useful for everyone due to large interindividual variability existing in VR suitability. To understand the neurobiological basis of this variability, we obtained neural structural and functional data from the participants using 3T magnetic resonance imaging. The participants completed one of two tasks (sports training or cognitive task) using VR, which diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…It has been reported that the feeling of being spatially located in the virtual environment differs between individuals and is related to differences in one's general spatial abilities (Coxon et al, 2016 ). More recently, it was also reported that there are individual differences in the rate of improvement through VR training in sports, and that these differences can be explained by differences in the structure of brain regions related to stereopsis and depth perception (Hosoda et al, 2021 ). In the current study, one of the ten batters showed a lower delta onset in VR than in the real environment (positioned at the upper left in Figure 2A ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the feeling of being spatially located in the virtual environment differs between individuals and is related to differences in one's general spatial abilities (Coxon et al, 2016 ). More recently, it was also reported that there are individual differences in the rate of improvement through VR training in sports, and that these differences can be explained by differences in the structure of brain regions related to stereopsis and depth perception (Hosoda et al, 2021 ). In the current study, one of the ten batters showed a lower delta onset in VR than in the real environment (positioned at the upper left in Figure 2A ).…”
Section: Discussionmentioning
confidence: 99%
“…Detecting this trait within the healthy population (whereby variability exists; Samuel et al, 2022 ) can improve screening and diagnostic protocols. Likewise, many remediation programs now employ virtual reality: suitability for these approaches is affected by structural variability in parietal areas (Hosoda et al, 2021 ). Assessing skills relying on parietal functioning may thus help singling out which individuals will benefit from these therapies.…”
Section: Discussionmentioning
confidence: 99%